FUNCTIONAL ASSESSMENT METHODS FOR SPINAL CORD INJURY PATIENTS IN REHABILITATION PROCESS – A SYSTEMATIC REVIEW - Eduardo, F.C.; Santos, E.L.; Santos, K.M.M.; Costa, J. C. M.; Vara, M.F.F.; Jung, M.F.; Machado, R.O.; Dias, T.Z. G. (ARACÊ, 2024)
Background: Spinal cord injury (SCI) leads to neurological damage that causes motor, sensory and autonomic neurologic functions decrease and/or loss. Evaluating the functionality of persons with SCI, especially in cases of incomplete injury, requires professional experience and skill. Objectives: This study aimed to gain a systematic overview of the functional assessment methods for SCI patients in the rehabilitation process. Search Methods: Systematic electronic searches were carried out using different databases from which 3489 registers were retrieved. Selection criteria: Studies that used tools to evaluate patients with SCI motor function as the manual test, Graded and Redefined Assessment of Strength, Sensibility, and Prehension (GRASSP), ASIA Impairment Scale (AIS), Neuromuscular Recovery Scale (NRS), Walking Index SCI (WISCI), Walking Index SCI II (WISCI-II), functional independence measure (FIM) or Spinal Cord Independence Measurement III (SCIM-III). Reviews, animal studies, articles with more than ten years, theses and dissertations and/or out of the object of study were excluded. Data collection and analysis: Two experienced professionals searched the databases. All titles were read for the first selection. Afterward, the abstracts were read, and another number of articles were excluded. In the end, ten articles met the inclusion criteria of this study. Main results: We identified different tools used for the functional assessment of SCI persons, but 9 out of 10 studies did not detail the results by segment, and none presented a manual test for trunk evaluation. Robotic therapy combined with conventional therapy brings good results. Final Considerations: Ten studies that met inclusion criteria were identified. It was noticed that more in-depth studies are needed detailing the tests by segment, especially on trunk functionality in people with different levels of SCI.